2022
DOI: 10.1016/j.mayocp.2021.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Ventilation in the Management of Respiratory Failure Due to COVID-19 Infection: Experience From a Resource-Limited Setting

Abstract: Introduction The role of NIV in SARS-CoV2 (COVID-19) related acute respiratory failure (C-ARF) is unclear. Methods C-ARF patients managed on NIV were categorised as NIV success or failure (death or intubation). Factors associated with failure were explored using regression analysis and expressed as Odds ratio (OR) with 95% Confidence Interval (CI). Results Between 1 st April 2020 and 15 th … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…An indirect evidence of CVS and renal involvement may be thought off by higher vasopressor use and higher incidence of AKI in failure group. Age has been the significant factor which was associated with NIV failure, this has been demonstrated in study by Chacko et al [18]. Age has been associated with poor outcomes, various reasons could be poor host defense mechanisms, multiple comorbidities and poor cardiovascular response to hypoxemia, increased risk of AKI.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…An indirect evidence of CVS and renal involvement may be thought off by higher vasopressor use and higher incidence of AKI in failure group. Age has been the significant factor which was associated with NIV failure, this has been demonstrated in study by Chacko et al [18]. Age has been associated with poor outcomes, various reasons could be poor host defense mechanisms, multiple comorbidities and poor cardiovascular response to hypoxemia, increased risk of AKI.…”
Section: Discussionmentioning
confidence: 85%
“…Age has been associated with poor outcomes, various reasons could be poor host defense mechanisms, multiple comorbidities and poor cardiovascular response to hypoxemia, increased risk of AKI. A summary of the studies predicting NIV failure is illustrated in Table 4 [13][14][15][16][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Chacko et al reported overall mortality in patients who required NIV was 30.1%. On adjusted analysis, mortality was associated with older age (OR, 1.08; 95% CI, 1.04 to 1.12), severe ARDS (OR, 4.04; 95% CI, 1.08 to 15.1), and higher peak D-dimer level (OR, 2.75; 95% CI, 1.19 to 6.37), requirement for intubation (OR, 9.36; 95% CI, 3.38 to 25.94), and need for inotropes and/or dialysis (OR, 9.19; 95% CI, 2.83 to 29.9) (3.1%) [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of these patients failing NIPPV, 20 (25.3%) died, while 21 were intubated (26.6%) [ 38 ]. Another study of 286 patients found NIPPV was successfully used without the need for intubation in 63.6% ( n = 182; 118 had moderate to severe ARDS) [ 39 ]. NIPPV failed in 82 patients (28.7%), and for patients in whom NIPPV failed and required mechanical ventilation, mortality was 78%.…”
Section: Discussionmentioning
confidence: 99%
“…NIPPV failed in 82 patients (28.7%), and for patients in whom NIPPV failed and required mechanical ventilation, mortality was 78%. Failure of NIPPV was more common in those with higher disease severity, lower admission PaO 2 /FiO 2 ratio, higher respiratory rates, and need for organ support [ 39 ].…”
Section: Discussionmentioning
confidence: 99%